MSP Guide - and Wageningen University (2015)
The MSP Guide Designing and facilitating effective multi-stakeholder partnerships Get started Download now The MSP Guide(EN, FR, ES) Explore the rationale, principles and process of designing and facilitating effective MSPs Get it now The MSP Tool Guide Detailed descriptions of 60 tried-and-tested tools to facilitate multi-stakeholder partnerships Get it now Reflection Methods: Practical Guide Proven…